A roadmap to vocational education and training around the world - Eichhorst, Werner [Verfasser]; Rodriguez-Planas, Núria [Verfasser]; Schmidl, Ricarda [Verfasser]; Zimmermann, Klaus F. [Verfasser] (My University, 2014)
"With young people among the biggest losers of the recent financial crisis, vocational education and training (VET) is often seen as the silver bullet to the youth joblessness problem. This paper provides a better understanding of VET around the world, proposing a typology with five types of vocational systems: (i) vocational and technical schools; (ii) vocational training centres; (iii) formal apprenticeships; (iv) dual apprenticeship systems combining school training with a firm-based approach; and (v) informal-based training. We first describe the strengths and challenges of each system. We subsequently review the evidence on the effectiveness of VET versus general education and between the different VET systems. There are clear indications that VET is a valued alternative beyond the core of general education, while various forms of apprenticeships combined with institutional learning tend to be more effective than school-based VET. Informal training is effective, however relatively little is known of its relative strengths compared with other forms of vocational education." (Author's abstract, BIBB-Doku)
Keywords: S System beruflicher Bildung; S 1.3.3 Vollzeitschulische Berufsausbildung; S 1.3 Berufliche Erstausbildung; L 2.1.1 Informelles Lernen; I 1 Internationale Berufsbildung; Berufsbildungssystem; Duales System; Anlernausbildung; Berufsausbildung; Schulische Berufsausbildung; Informelles Lernen; Effektivität